Multiple eco-regions contribute to the seasonal cycle of Antarctic aerosol size distributions - J. Brean; D. C. S. Beddows; E. Asmi; A. Virkkula; A. Virkkula; L. L. J. Quéléver; M. Sipilä; F. Van Den Heuvel; T. Lachlan-Cope; A. Jones; M. Frey; A. Lupi; et al. (Atmospheric Chemistry and Physics)
In order to reduce the uncertainty of aerosol radiative forcing in global climate models, we need to better understand natural aerosol sources which are important to constrain the current and pre-industrial climate. Here, we analyse particle number size distributions (PNSDs) collected during a year (2015) across four coastal and inland Antarctic research bases (Halley, Marambio, Dome C and King Sejong). We utilise k-means cluster analysis to separate the PNSD data into six main categories. “Nucleation” and “bursting” PNSDs occur 28 %–48 % of the time between sites, most commonly at the coastal sites of Marambio and King Sejong where air masses mostly come from the west and travel over extensive regions of sea ice, marginal ice and open ocean and likely arise from new particle formation. “Aitken high”, “Aitken low” and “bimodal” PNSDs occur 37 %–68 % of the time, most commonly at Dome C on the Antarctic Plateau, and likely arise from atmospheric transport and ageing from aerosol originating likely in both the coastal boundary layer and free troposphere. “Pristine” PNSDs with low aerosol concentrations occur 12 %–45 % of the time, most commonly at Halley, located at low altitudes and far from the coastal melting ice and influenced by air masses from the west. Not only the sea spray primary aerosols and gas to particle secondary aerosol sources, but also the different air masses impacting the research stations should be kept in mind when deliberating upon different aerosol precursor sources across research stations. We infer that both primary and secondary components from pelagic and sympagic regions strongly contribute to the annual seasonal cycle of Antarctic aerosols. Our simultaneous aerosol measurements stress the importance of the variation in atmospheric biogeochemistry across the Antarctic region.